Stalin’s biblical hermeneutics: from 2 Thessalonians 3 to Acts 4 - Boer, Roland (Journal of the bible and its reception, 2017)
This article concerns the creative reinterpretation of two biblical texts in the thought of Joseph Stalin: 2 Thessalonians 3:10 and Acts 4:32 and 35. Indeed, “anyone unwilling to work should not eat” became the hermeneutical frame through which the text from Acts 4, “everything they owned was held in common (…) They laid it at the apostles’ feet, and it was distributed to each as any had need,” was reinterpreted. Already from 1917, the text of 2 Thessalonians was used by Lenin to define what would soon be called socialism, in distinction from communism (the distinction was itself a Bolshevik innovation). Stalin would make much greater use of the text, extending the sense of those not working – the idle capitalists and bourgeoisie – to those who lagged behind in the project of creating socialism. Further, it became the interpretive key for reworking the communist slogan, “from each according to ability, to each according to need” (itself a gloss on Acts 4) into a slogan for socialism, “from each according to ability, to each according to work.” These two forms of the slogan became the means to distinguish socialism from communism. The result of this process of biblical reinterpretation was the appearance of both biblical texts – one quoted and one glossed – in the “Stalin” Constitution of 1936. Throughout I seek to understand Stalin’s thought on the basis of his writings, without taking sides in the perpetual polarization over his legacy.